Growth of garment industry in Bangladesh : economic and social dimensions : proceedings of a National Seminar on Ready-made Garment Industry, held in Dhaka, Bangladesh, January 21-22, 2000 - Paul-Majumder, Pratima; Sen, Binayak (Bangladesh Institute of Development Studies, 2001)
Seminar organized by Bangladesh Institute of Development Studies with assistance from Oxfam GB.